Screening and management practices for renal disease in the HIV‐positive patient population of an inner metropolitan sexual health service. Issue 2 (February 2017) - Kakar, Sheena; Drak, Douglas; Amin, Tahiya; Cheung, Jason; O'Connor, Catherine C; Gracey, David M
Abstract: Renal disease is an important and commonly encountered co‐morbidity in HIV infection. Despite this, few data are available concerning renal disease in this patient group. A retrospective review was conducted of all HIV‐positive patients of an inner metropolitan sexual health service who attended from 1 August 2013 to 31 July 2014 for HIV management. One hundred eighty‐eight HIV‐positive patients attended the clinic during the study period. The majority were male (96%), Caucasian (70%) and 30–39 years of age (37%). There was a high prevalence of renal risk factors in the population, including potentially nephrotoxic antiretroviral therapy (61%), smoking (38%), hypertension (12%), dyslipidemia (11%) and hepatitis C co‐infection (7%). In the previous year, measurements of estimated glomerular filtration rate were performed in all patients, but measurements of lipid profiles, urinary protein and serum phosphate were performed within the last year in only 48%, 33% and 30% of patients, respectively. These are the first comprehensive data regarding renal disease, associated risk factors and screening and management practices in the HIV‐positive patient population of a specialized sexual health service in Australia. This patient population demonstrates a particularly high prevalence of risk factors for renal disease. Despite this, screening investigations were not performed as recommended. This represents a potential area to improve patient care. Summary at a Glance: The authors demonstrate a high burden of risk factors for renal disease amongst HIV‐infected patients with room for improvement in current screening practices.